The native ORAI channel trio underlies the diversity of Ca(2+) signaling events - Yoast, Ryan E. (Nat Commun, 2020)
The essential role of ORAI1 channels in receptor-evoked Ca(2+) signaling is well understood, yet little is known about the physiological activation of the ORAI channel trio natively expressed in all cells. The roles of ORAI2 and ORAI3 have remained obscure. We show that ORAI2 and ORAI3 channels play a critical role in mediating the regenerative Ca(2+) oscillations induced by physiological receptor activation, yet ORAI1 is dispensable in generation of oscillations. We reveal that ORAI2 and ORAI3 channels multimerize with ORAI1 to expand the range of sensitivity of receptor-activated Ca(2+) signals, reflecting their enhanced basal STIM1-binding and heightened Ca(2+)-dependent inactivation. This broadened bandwidth of Ca(2+) influx is translated by cells into differential activation of NFAT1 and NFAT4 isoforms. Our results uncover a long-sought role for ORAI2 and ORAI3, revealing an intricate control mechanism whereby heteromerization of ORAI channels mediates graded Ca(2+) signals that extend the agonist-sensitivity to fine-tune transcriptional control.